Peran Pendidikan Multikultural Dalam Menanggulangi Diskriminasi Dan Intoleransi Di Kalangan Siswa Sekolah Dasar - Barbara Andrean; Sestya Fharadilla; Amelia Amelia (Prodi PGSD Unsultra, 2023)
The diversity of cultures, religions, and ethnicities in Indonesia is a valuable asset but often becomes a source of conflict, especially in elementary school environments. Multicultural education is an essential approach to addressing discrimination and intolerance among students by instilling values of respect for diversity from an early age. This study aims to analyze the role of multicultural education in mitigating discrimination and intolerance through structured implementation in elementary school settings. The research method used is qualitative with a case study approach. Data were collected through in-depth interviews, participatory observations, and document analysis from three elementary schools with diverse student backgrounds. The results of the study indicate that systematically designed multicultural education can enhance students' understanding of diversity, reduce negative stereotypes, and build stronger tolerance among students. This research contributes to the development of multicultural-based curricula and teacher training to create inclusive learning environments.